Parameter kinetika reaksi dekomposisi katalitik metana menjadi karbon nanotube dengan katalis Ni-Cu-Al - Praswasti PDK Wulan; Widodo W Purwanto; Yuswan Muharam; Anindya Adiwardhana (Jurnal Teknik Kimia Indonesia, 2012)
Kinetic Parameter of Methane catalytic Decomposition Reaction into Nanotube Carbon with Ni-Cu-Al Catalyst. Development of production technology of nanotubes carbon through catalytic conversion of hydrocarbons will be efficient and effective if based on knowledge of the nucleation and growth mechanism of carbon nanotubes. Most of the research that focused on identifying the main products of reaction and estimate the activation energy. Growth kinetics and mechanism data of carbon nanotubes not completely available, so that process kinetics models are always based on experimental kinetic data. The objective of this research is to obtain kinetic parameters of catalytic decomposition of methane using the catalyst Ni-Cu-Al with composition of 2:1:1 which was prepared by co-precipitation method using natrium carbonate solution precipitant. Experimental kinetic data were taken in the temperature range of 650-750 °C and pressure of 1 atmosphere. Kinetic data were tested by micro-kinetic model derived from the catalytic surface reaction mechanism. The most appropriate kinetic model with experimental result is the adsorption stage which shows that consumption of intermediate (reaction surface) faster than the formation of intermediate (adsorption of methane). Kinetic parameters obtained are activation energy of 40,6 kJ/mole and pre-exponential factor of 8,625 x 106. Keywords: methane decomposition, hydrogen, carbon nanotubes, co-precipitation, kinetics of reactionAbstrak Pengembangan teknologi produksi karbon nanotube melalui konversi katalitik hidrokarbon akan efisien dan efektif jika didasarkan pada pengetahuan mekanisme nukleasi dan pertumbuhan karbon nanotube. Sebagian besar studi melakukan riset yang difokuskan pada identifikasi produk utama reaksi dan estimasi energi aktivasi. Data kinetika dan mekanisme pertumbuhan karbon nanotube tidak tersedia dengan lengkap sehingga model kinetika proses selalu didasarkan pada data kinetika eksperimen. Pada penelitian ini, dilakukan studi untuk memperoleh parameter kinetika reaksi dekomposisi katalitik metana menggunakan katalis Ni-Cu-Al dengan target komposisi 2:1:1 yang dipreparasi dengan metode kopresipitasi menggunakan presipitan larutan natrium karbonat. Data kinetika eksperimen diambil pada rentang temperatur 650-750 oC dan tekanan 1 atmosfer. Data kinetika diuji dengan model kinetika mikro yang diturunkan dari mekanisme reaksi permukaan katalis. Model kinetika yang paling sesuai dengan hasil percobaan adalah tahap adsorpsi yang menunjukkan bahwa konsumsi intermediate (reaksi permukaan) lebih cepat dari pembentukan intermediate (adsorpsi metana). Parameter kinetika yang diperoleh berupa Energi aktivasi sebesar 40,6 kJ/mol dan faktor pre-eksponensial 8,625 x 106.Kata kunci: dekomposisi metana, hidrogen, karbon nanotube, kopresipitasi, kinetika reaksi